Social order: traditions and contemporary approaches to study - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article analyzes main traditional and contemporary approaches to the study of problem of social order. The author explicates that idea of certain form of order as a basis for existence of state and society is presented in Confucianism and in Antiquity. Interpretation of social order in theory of civil contract and its specific in works by Th. Hobbes, J. Locke, J.-J. Rousseau is shown. Peculiarities of explication of mechanisms of formation of social order by classical authors insociology A. Comte, H. Spencer, F. Tönnies, E. Durkheim, M. Weber, T. Parsons are analyzed. Special attention is paid to the works of N. Elias, P. Bourdieu, A. Giddens, P. Berger, Th. Luckmann. The main conclusion is that contemporary reality needs further elaboration of theoretical, methodological and practical problems of constitution and support of social order.
Keywords: society; social order; organization of social life; theory of social contract; social statics; social dynamics; social action; social interaction; social stability